2019
DOI: 10.1007/s40243-019-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low loading of platinum in proton exchange membrane-based fuel cells: a brief review

Abstract: This review report summarizes different synthesis methods of PEM-based fuel cell catalysts with a focus on ultra-low loading of Pt catalysts. It also demonstrates fuel cell performances with ultra-low loading of Pt catalysts which have been reported so far, and suggests a combination method of synthesis for an efficient fuel cell performance at a low loading of Pt catalyst. Here, maximum mass-specific power density (MSPD) values are calculated from various reported performance values and are discussed, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 95 publications
1
32
0
1
Order By: Relevance
“…Esses NC combinam vantagens comuns a outros sistemas, tais como lipossomas e nanopartículas poliméricas, incluindo a possibilidade de carrear fármacos de diferentes características em seu interior e, semelhante aos lipossomas e nanoemulsões, apresentam em sua composição excipientes lipídicos. 69 As nanopartículas lipídicas sólidas são nanoesferas compostas de um núcleo lipídico sólido. Assim como as nanopartículas poliméricas, a sua matriz sólida pode proteger eficientemente os ativos farmacêuticos contra a degradação química e proporcionar modificação dos perfis de liberação do fármaco.…”
Section: Nanopartículas Lipídicas Sólidas E Carreador Lipídico Nanoesunclassified
“…Esses NC combinam vantagens comuns a outros sistemas, tais como lipossomas e nanopartículas poliméricas, incluindo a possibilidade de carrear fármacos de diferentes características em seu interior e, semelhante aos lipossomas e nanoemulsões, apresentam em sua composição excipientes lipídicos. 69 As nanopartículas lipídicas sólidas são nanoesferas compostas de um núcleo lipídico sólido. Assim como as nanopartículas poliméricas, a sua matriz sólida pode proteger eficientemente os ativos farmacêuticos contra a degradação química e proporcionar modificação dos perfis de liberação do fármaco.…”
Section: Nanopartículas Lipídicas Sólidas E Carreador Lipídico Nanoesunclassified
“…As a solution, increasing platinum (Pt) catalyst loading can accelerate the reaction, but limitations in scalability and economic feasibility restrict engineering of high Pt loading. As a result, numerous studies on PEMFCs have focused on development of optimized catalyst coated membranes (CCM) and MEA layout with high catalyst utilization applying strategies such as (i) increasing Pt loading [3][4][5], and (ii) graded catalyst loading [6,7]. Yet, fulfilling the Department of Energy (DOE) targets is an ongoing endeavor [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in References efficient PEMFC anodes were prepared with 14 to 22 μg Pt cm −2 ; our research group has recently reported highly efficient HOR catalysts with only a few μg cm −2 of the noble metal . However, in majority of currently used PEMFC systems the Pt loadings in anode catalysts capable of practically usable lifetimes are in the range of 0.2 to 0.5 mg cm −2 ; further reduction of Pt content often leads to issues of limited durability or mass transport limitations . No long‐term durability tests under heavy‐duty operation conditions have been presented so far for the anodes with extremely low (μg cm −2 range) platinum contents, which is the aim of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite of development of noble metal free electrodes (using, for example, nickel nitrides, 6 cobalt, 7 nickel-copper alloys, 8 metal [oxy] sulfides, 9 or even metal-free carbon catalysts 10 ) the Ptbased catalysts still remain the most efficient and most widely used catalytic elements for PEMFC. 11 Another strategy is thus a development of materials with almost negligible amounts of highly dispersed noble metal particles [11][12][13][14] or their alloying with other cheaper metals, 15,16 which may reach the industrial requirements for sustainable and affordable FC systems. In PEMFC the kinetics of hydrogen oxidation reaction (HOR) is significantly faster than that of oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation